Cannabinoid type 2 receptor agonist JWH-133, attenuates Okadaic acid induced spatial memory impairment and neurodegeneration in rats - Cakir, Murat; Tekin, Suat; Doganyigit, Zuleyha; Erden, Yavuz; Soyturk, Merve; Ciğremiş, Yılmaz; Sandal, Suleyman; Erden, Yavuz (Pergamon-Elsevier Science Ltd, 2019)
Aim: Cannabinoid system has various physiological roles such as neurogenesis, synaptic plasticity and emotional state regulation in the body. The presence of cannabinoid type 2 receptor (CB2), a member of the cannabinoid system, was detected in different regions of the brain. CB2 receptor plays a role in neuroinflammatory and neurodegenerative processes. We aimed to determine the possible effect of CB2 agonist JWH-133 in Okadaic acid (OKA)-induced neurodegeneration model mimicking Alzheimer's Disease (AD) through tau pathology. Materials and methods: In this study, 40 Sprague Dawley male rats were divided into 4 groups (Control, Sham, OKA, OKA + JWH-133). Bilateral intracerebroventricular (icv) injection of 200 ng OKA was performed in the OKA group. In the OKA + JWH-133 group, injection of JWH-133 (0.2 mg/kg) was performed intraperitoneally for 13 days different from the group of OKA. Morris water maze test was used to evaluate the spatial memory. Levels of caspase-3, phosphorylated tau (ser396), amyloid beta (A beta), tumor necrosis factor-alpha (TNF-alpha) and interleukin-1 beta (IL-1 beta) levels in brain cortex; and the hippocampus regions were examined by immunohistochemical methods. Key findings: In the OKA group, caspase-3, phosphorylated tau (ser396), A beta, IL-1 beta levels were higher in the cortex and hippocampus than in the other groups. The implementation of the JWH-133 reversed the increments in these parameters, and also prevented spatial memory impairment.
Keywords: Alzheimer's Disease; Okadaic Acid; Cannabinoid Type 2 Receptor; Jwh-133